تحليل الحركة المرورية على الشريانات المدينية المنظمة بإشاراتٍ ضوئيةٍ - رستم, أكرم; أسعد, شذى; خازم, رين (Latakia University Journal -Engineering Sciences Series, 2019)
يقدم هذا البحث تقييماً للحركة المرورية على الشريانات المدينية المنظّمة بإشاراتٍ ضوئيةٍ، التي يمكن اعتبارها محاور ربط رئيسة للحركة بين المناطق والتجمعات الرئيسة في المدينة وبين مركز المدينة, كما تشكل محاور حركة أساسية تربط المدينة مع محيطها، فإن تحسين الوضع المروري على هذه الشريانات سيكون له تأثير كبير على رفع أداء هذه المحاور وتخفيض الضياعات الزمنية, كما يمكن أن يكون له منعكسات بيئية مهمّة مثل تقليل انبعاث الملوثات وتخفيف الضجيج الناجم عن الحركات المرورية. لقد أجريت الدراسة المرورية على طريقٍ شريانيٍ في مدينة طرطوس لتعيين مستوى خدمة هذا الطريق الشرياني وفق معايير دليل السعة الأمريكي (HCM2000) Highway capacity Manual، وقد وجد أن هذه المعايير المستخدمة في عملية التقييم لاتعكس تقييماً حقيقياً وواقعياً لمستوى خدمة مثل هذه الطرق، لذلك سوف يتم في هذا البحث اقتراح تطوير تلك المعايير بشكل يلائم الواقع الهندسي والمروري للشريانات في الظروف المحلية للمدن السورية بإدخال تأثير وجود الطرق الفرعية والحركات الجانبية التي تشكل جزءاً كبيراً من الحركة على هذه المحاور بهدف تطويرها وبحيث تخدم غزارة المرور العالية بين المراكز الفعّالة النشطة في المدينة. This research offers a traffic assessment of the urban arterials controlled by traffic lights. These arterials form the main traffic links between regions and principal clusters in the city, and the city centers. They also form major traffic routes connecting the city with its surroundings. Therefore, traffic improvements on these arterials will have a significant effect on increasing their performance, decreasing time loss, and may have significant environmental effects, such as decreasing the emission of pollutants, and noises resulting traffic. This study was done on an arterial in the city of Tartus. It adopted the American parameters guide for traffic capacity (Highway Capacity Manual) - HCM2000 in determining the arterial’s level of service. The study showed that the HCM2000 parameters used in the assessment did not give a realistic assessment of the arterial’s true level of service. This research aims to develop these parameters to fit the actual traffic and geometrical conditions of these arterials under present local conditions of the Syrian cities. The effect of streetscape and side traffic which form a major part of the traffic on these arterials was accounted for, with the purpose of developing arterials to accommodate the high traffic and from crowded city centers.